Survival of Family Businesses in Cameroon: Evaluating the Role of Succession Planning - Jeff Astein M. Fokam; Jawea Smith Ekonje (European Scientific Journal, ESJ, 2026)
This study examined the effect of succession planning on the survival of family businesses in Yaoundé. The main objective was to investigate how education and training, mentoring, and entrepreneurial orientation influence the sustainability of family enterprises. A descriptive and quantitative research design was employed, and data were collected through questionnaires administered to 106 respondents across selected family businesses. The findings revealed that education and training (β = 0.233, p < 0.05) and entrepreneurial orientation (β = 0.389, p < 0.01) significantly and positively influence the survival of family businesses. Mentoring, however, showed a positive but statistically insignificant effect (β = 0.192, p > 0.05). The results further established that succession planning is crucial for ensuring the continuity of family enterprises, though many lack formal written plans. The study concludes that succession planning, when structured and formalized, enhances business survival by preparing competent successors and minimizing family conflicts. It recommends that family businesses in Yaoundé invest in education and training programs, encourage entrepreneurial orientation, and institutionalize succession planning policies to ensure intergenerational sustainability.